2018
DOI: 10.1002/elps.201700443
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of ruthenium anticancer agents by MEEKC‐UV and MEEKC–ICP‐MS: Impact of structural motifs on lipophilicity and biological activity

Abstract: We present here the first comprehensive study on the lipophilicity of ruthenium anticancer agents encompassing compounds with broad structural diversity, ranging from octahedral Ru (azole) through to Ru (arene) complexes. MEEKC was used to determine the capacity factors of the Ru complexes, and after a complex peak was unambiguously assigned using MEEKC-ICP-MS, the results were validated through comparison with the log P determined by octanol/water partitioning experiments. Correlation of the two data sets dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 51 publications
(70 reference statements)
0
3
0
Order By: Relevance
“…Partitioning of the test compound is between an aqueous phase and a non-polar organic microemulsion phase. Standard calibration curves are also drawn as in the RP-HPLC method and the test compound retention time is compared to the calibration curve for lipophilicity determination [49][50][51].…”
Section: Capillary Electrophoresis Logp and Logd X Determination Methodmentioning
confidence: 99%
“…Partitioning of the test compound is between an aqueous phase and a non-polar organic microemulsion phase. Standard calibration curves are also drawn as in the RP-HPLC method and the test compound retention time is compared to the calibration curve for lipophilicity determination [49][50][51].…”
Section: Capillary Electrophoresis Logp and Logd X Determination Methodmentioning
confidence: 99%
“…Identification of the adducts was confirmed using CE coupled to a Bruker microTOF-Q II ES-MS instrument. A third study by the group, once again used CE-ICP-MS with coupling using the CSFI, but this time to explore the lipophilicity and biological activity of Ru-anticancer drugs using microemulsion electrokinetic chromatography (MEEKC) 218 . This micelle-based separation method uses a phosphate buffer with addition of SDS, 1-butanol and heptane, with sonication to produce microemulsion oil droplets, which act as a stationary phase.…”
Section: Metallodrug Speciationmentioning
confidence: 99%
“…In this paper, we extend the combined MD/COSMOmic approach to investigate the partition coefficients of solutes in a heptane/butanol/sodium dodecyl sulfate (SDS) in water microemulsion. The SDS/butanol/heptane in water microemulsion has a wide range of applications in separation science, such as chiral separation of enantiomeric analytes, separation of highly hydrophobic compounds, , partition coefficients determination, biomembrane permeability, and lipophilicity determination. , Ishihama et al showed that solute partitioning in this microemulsion is different from that in octanol/water and micellar systems but similar to that in gel-phase liposome systems. In this work, MD simulations are performed to obtain self-assembled heptane/butanol/SDS in water droplets, at the same concentration range reported by Ishihama et al The partition coefficients of 14 chemicals between the simulated droplets and water are subsequently predicted using COSMOmic.…”
Section: Introductionmentioning
confidence: 99%